PENGARUH PEMBERDAYAAN SDM DAN LINGKUNGAN KERJA TERHADAP KEPUASAN PEKERJA PEGAWAI PADA BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBERDAYA MANUSIA KABUPATEN OGAN KOMERING ULU - Muhammad Apriliansyah Rahmadhani; Nadila Oktarina (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2023)
This research discussed about. The Influence of Human ResourceEmpowerment and Work Environment on Employees' Job Satisfaction at theAgency for Personnel and Human Resources Development, Ogan KomeringUlu Regency. The data collection technique used in this study was through thedistribution of questionnaires. The total population was 61 people. Theanalytical method used was multiple linear regression. The results showedthat partially HR Empowerment and work environment had a significantinfluence on Employees'Job Satisfaction at the Agency for Personnel andHuman Resources Development, Ogan Komering Ulu Regency. F count was66.602 with Ftable 3.16. So Fcount > Ftable or 66,602 > 3,16, then thedecision Ho was rejected Ha was accepted, meaning that all X variables,namely HR Empowerment (X1) and Work Environment (X2) together had asignificant influence on Employees'Job Satisfaction at the Personnel andResource Development Agency. Human Resources of Ogan Komering UluRegency. The value of the coefficient of determination (R Square) was 0.697%,this showed that 69.7% of the contribution from Employees' Job Satisfaction atthe Agency for Personnel and Human Resources Development of OganKomering Ulu Regency can be explained by the variables of HR Empowerment(X1) and Work Environment ( X2), while the remaining 30.3% was influencedby other variables besides the variables in this study, such as motivation, workinvolvement, absenteeism, turnover, feelings of stress, workperformance/performance (Afandi, 2018:77-78).